2021
DOI: 10.1088/1742-6596/1879/2/022080
|View full text |Cite
|
Sign up to set email alerts
|

Personal identification system based on multi biometric depending on cuckoo search algorithm

Abstract: In modern devices, many personal identification systems are used using various biometrics to confirm the identity of an individual and identify him for several purposes. Some of these essential biometrics are used in this paper to help identify a person while attaining social distance because of the widespread epidemics. The features of the face, eyes, nose, and finally, the features of the mouth are used in this article. The work begins by detecting the parts of multibiometric from the input images using Viol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In another research [51], the face, eyes, mouth and nose were used to identify people using the intelligent cuckoo search algorithm, Fig. Here in table 2 some of these properties of last five years:…”
Section: Facementioning
confidence: 99%
“…In another research [51], the face, eyes, mouth and nose were used to identify people using the intelligent cuckoo search algorithm, Fig. Here in table 2 some of these properties of last five years:…”
Section: Facementioning
confidence: 99%
“…One of these studies is the use of the neural aggregation network algorithm [12], convolutional neural networks (CNN), and deep convolutional neural networks, the following is a comparison between these studies and the proposed method as shown in Table 2. This research aims to discover an effective method for determining the area of the human face in video sequences by using the important improvements made to Viola Jones' face detection algorithm [17] that determines the facial area in digital images while not allowing the loss of the facial area to occur. This method can be used in many important applications such as browsing the video, identifying the face of people in the videos for crime detection, and indexing the video.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the wrong acceptance rate (6) in this system was 5%, meaning that any radiograph that does not exist in the radiograph dataset of the systemis not accepted. And this was done according to the following formula [27], [28]:…”
mentioning
confidence: 99%